SOSIALISASI PENDIDIKAN POLITIK MENYONGSONG PEMILU 2024 TERHADAP GENERASI Z DI SMAN 4 YOGYAKARTA - Iswardhana, Muhammad Ridha; Arisanto, Puguh Toko; Chusnul Chotimah, Hidayat; Wibawa, Adi; Risky, Lucitania; Setyo Pratiwi, Tiffany (Jurnal Abdi Masyarakat Multidisiplin, 2023)
Abstract Political participation in democratic countries, such as Indonesia, is still not considered high during general election. Influenced by various factors, many people choose not to vote “golput” during election. One way to reduce the number of golput is to provide political education to the public. Generation Z, as first-time voters in the 2024 election in Indonesia, should be given political education to reduce the golput-rate during the democratic process. Generation Z is expected to become politically aware of the political situation, the consequences of golput, and the importance of participation in the 2024 election. At the same time, strengthening political education aims to ensure that Generation Z not only becomes political objects but also political subjects. Therefore, the International Relations Program at Universitas Teknologi Yogyakarta carried out a project to provide political education in preparation for the 2024 election at a senior high school, Sekolah Menengah Atas Negeri (SMAN) 4 Yogyakarta.   Keywords: Political Participation, Election, Political Education, Golput, Generation Z.   Abstrak   Partisipasi politik pada waktu pemilihan umum di negara demokrasi yakni Indonesia masih belum bisa dikatakan tinggi. Dipengaruhi oleh beberapa faktor, banyak masyarakat yang memilih golongan putih (golput) pada waktu pemilu. Salah satunya upaya menguranginya adalah dengan diadakannya pendidikan politik kepada masyarakat. Generasi Z sebagai calon pemilih pemula untuk pemilu 2024 adalah generasi yang patut diberikan pendidikan politik guna mengurangi tingkat golput pesta demokrasi tersebut. Generasi Z diharapkan menjadi generasi yang melek politik terhadap situasi politik, sanksi atas golput, dan pemahaman mengenai pentingnya partisipasi dalam Pemilu 2024. Di sisi yang sama, penguatan pendidikan politik juga dimaksudkan agar generasi Z tidak hanya menjadi objek politik tetapi juga berperan sebagai subjek politik.  Oleh sebab itu, prodi Ilmu Hubungan Internasional, Universitas Teknologi Yogyakarta melakukan pengabdian mengenai pendidikan politik menyongsong pemilu 2024 di Sekolah Menengah Atas Negeri (SMAN) 4 Yogyakarta.